2017
DOI: 10.5603/cj.a2017.0033
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of coronary artery disease severity in lower extremity artery disease patients: A correlation study of TASC II classification, Syntax and Syntax II scores

Abstract: Taking into account all lower limb arterial segments for predicting CAD during lower limb arterial angiography was recommended. A TPS of more than '6' is the practical cut-off value for estimating severe CAD. Femoropopliteal arterial critical stenosis is the most predictive arterial zone for estimating severe CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Vuruskan et al found that angiographic critical stenosis in femoro-popliteal segment was most reliable for the determination of subjects with high SS [30]. In the present study, significant and total occlusion of the femoro-popliteal segment arteries by DUS were found in significantly more proportion of subjects with high SS (p = 0.02).…”
Section: Distribution Of Leadsupporting
confidence: 57%
See 1 more Smart Citation
“…Vuruskan et al found that angiographic critical stenosis in femoro-popliteal segment was most reliable for the determination of subjects with high SS [30]. In the present study, significant and total occlusion of the femoro-popliteal segment arteries by DUS were found in significantly more proportion of subjects with high SS (p = 0.02).…”
Section: Distribution Of Leadsupporting
confidence: 57%
“…com) was used to deduce the SS [11]. The SS was graded into low (0-22), intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) and high (> 32) risk.…”
Section: Cad and Ssmentioning
confidence: 99%
“…Furthermore, several studies reported that patients with an abnormal ankle-brachial index, greater carotid artery intima media thickness, or greater carotid artery stenosis have more complex CAD [28][29][30][31]. Moreover, a recent study observed an association of total peripheral score, which evaluated the extent of lower-extremity artery disease, with SYNTAX score [32]. The panvascular inflammatory process observed in our study is consistent with previous findings.…”
Section: Oct Findingssupporting
confidence: 92%
“…[40][41][42] A relationship between PAD and increased SXscore has also been shown. 43,44 Increased rates of PAD and higher cIMT may explain why SXscore increases in patients with ATC.…”
Section: Discussionmentioning
confidence: 99%